Myocardial Infarction with Non-obstructive Coronary Arteries - MINOCA in Young Patients - Gulana Aghayeva; Narmin Islamova; Anakhanim Safarli (Caucasian Medical Journal)
Myocardial infarction with non-obstructive coronary arteries or MINOCA, is not associated with severe coronary artery stenosis. According to statistics, MINOCA occurs more frequently in women and younger patients. Symptoms and signs are similar to acute myocardial infarction. Coronary artery stenosis was excluded by coronary angiography.